Comparison Analysis of Transformer Boosting and Induced Degeneration Topology Design of LNA for Millimeter Wave Frequency Range Using Polymeric Substrates - Nitin Agarwal (International Journal of Electrical and Communication Engineering Technology, 2025)
In this study, a comparison between transformer boosting and source degeneration LNA topologies is conducted using two polymeric substrates—Polyimide (PI) and Liquid Crystal Polymer (LCP)—for millimeter-wave (mmWave) applications. With growing interest in flexible and high-frequency electronics, polymeric materials offer unique advantages such as low dielectric constants, mechanical flexibility, and thermal stability. The analysis explores gain, return loss, and noise figure performance while evaluating the influence of dielectric properties on the RF behavior of the LNAs. The simulation is performed using industry-standard tools, and the findings provide insights into optimizing LNA topologies for future polymer-based RF systems. Full-wave electromagnetic simulations and circuit- level modeling were carried out to evaluate key performance metrics including gain (S21), noise figure (NF), input/output matching (S11/S22), and power efficiency. The influence of polymer dielectric constant, loss tangent, and surface roughness on the LNA's performance was analyzed in detail, offering insights into the structure-property-performance relationship of polymer-supported mmWave circuits. Results demonstrate that polymer-based substrates can significantly affect the impedance matching and overall noise behavior of mmWave amplifiers. This research highlights the potential of functional polymer materials in the fabrication and optimization of high-frequency RF components and offers a pathway for integrating polymer science with mmWave circuit design for emerging flexible, wearable, and bio-integrated communication systems
Keywords: CMOS LNA; Induced Degeneration Topology; MM- Wave; NF; Transformer boosting technique; polyimide (PI) and liquid crystal polymer (LCP)